Targeting Dendritic Cells in vivo for Cancer Therapy - Caminschi, Irina; Maraskovsky, Eugene; Heath, William R. (Frontiers in Immunology, 2012)
Monoclonal antibodies that recognize cell surface molecules have been used deliver antigenic cargo to dendritic cells (DC) for induction of immune responses. The encouraging anti-tumor immunity elicited using this immunization strategy suggests its suitability for clinical trials. This review discusses the complex network of DC, the functional specialization of DC subsets, the immunological outcomes of targeting different DC subsets and their cell surface receptors, and the requirements for the induction of effective anti-tumor CD4 and CD8 T cell responses that can recognize tumor-specific antigens. Finally, we review preclinical experiments and the progress toward targeting human DC in vivo.